Spotted Wing Drosophila in Florida Berry Culture - Lindsy E. Iglesias; James F. Price; Craig R. Roubos; Justin M. Renkema; Oscar E. Liburd (EDIS)
Spotted wing drosophila, Drosophila suzukii (Matsumura) (Diptera: Drosophilidae), is an invasive pest that was introduced into Florida in 2009. Spotted wing drosophila survives well under Florida’s climatic conditions. In 2014, losses to berry crops in Florida were estimated at $35 million. Losses are due to maggot-infested fruit, which is unacceptable for the fresh berry market, and puncture holes in the fruit made by egg-laying females. The holes lead to secondary infection by fungal and bacterial pathogens. This revised 5-page fact sheet describes the flies and some strategies to identify them and manage them in berry operations. Written by Lindsy E. glesias, James F. Price, Craig R. Roubos, Justin M. Renkema, and Oscar E. Liburd, and published by the Department of Entomology and Nematology, January 2016.